"They're just students. There's no clear distinction": A critical discourse analysis of color-evasive, gender-neutral faculty discourses in undergraduate calculus instruction. Issue 4 (20th October 2022) - McNeill, R. Taylor; Leyva, Luis A.; Marshall, Brittany
ABSTRACT: Background: Calculus instruction is underexamined as a source of racialized and gendered inequity in higher education, despite research that documents minoritized students' marginalizing experiences in undergraduate mathematics classes. This study fills this research gap by investigating mathematics faculty's perceptions of the significance of race and gender to calculus instruction at a large, public, historically white research university. Methods: Theories of colorblind racism and dysconsciousness guided a critical discourse analysis of seven undergraduate calculus faculty's perceptions of instructional events. Findings: Our analysis revealed two dominant discourses: (i) Race and gender are insignificant social markers in undergraduate calculus; and (ii) Instructional events can be objectively deemed race- and gender-neutral. We illustrate how calculus faculty varyingly engaged these colorblind discourses as well as discourses that challenged such conceptions of instruction. We also highlight how faculty dysconsciousness in reports of instructional practices reflect potential operationalization of dominant discourses that reinforce colorblind racism. Contribution: With limited research on faculty perspectives on racial equity in mathematics, our study documents how color-evasive, gender-neutral discourses among mathematics faculty shape orientations to instruction that reinforce the gatekeeping role of calculus in STEM higher education. Implications are provided for race- and gender-conscious undergraduate mathematics instruction and faculty development.